A Real‐World Evidence Framework for Optimizing Dosing in All Patients With COVID‐19. Issue 5 (29th June 2020) - Peck, Richard W.; Weiner, Daniel; Cook, Jack; Robert Powell, J.
Abstract : Potential treatments for coronavirus disease 2019 (COVID‐19) are being investigated at unprecedented speed, and successful treatments will rapidly be used in tens or hundreds of thousands of patients. To ensure safe and effective use in all those patents it is essential also to develop, at unprecedented speed, a means to provide frequently updated, optimal dosing information for all patient subgroups. Success will require immediate collaboration between drug developers, academics, and regulators.